Use of system interdependency to allocate component reliability. (29th August 2007) - Vaidya, Omkarprasad S.; Kumar, Sushil
This paper presents a methodology to allocate reliability to system components on the basis of system interdependency. This approach may be used when the system performance is considered to be more important than the cost factor. Reliability allocation is carried out based on the relative importance of the tasks of the components in the system that define the system interdependency. This interdependency-based system reliability allocation approach is based on the Analytic Hierarchy Process (AHP) and the numerical computation methods at various stages, and supports the hierarchical structure present in the system. The methodology is developed explaining the concept of system dependency, and elucidated by a hypothetical and a practical example.